The Results of Research of Magnetic Fluid Nanoparticles by Microscopy and X-ray Methods - A.M. Storozhenko; I.A. Shabanova; A.O. Tantsyura (Журнал нано- та електронної фізики)
This is a researching of dispersed, elemental and phase composition of magnetic fluids. Samples of magnetic fluids based on kerosene and vacuum oil are the objects of study. As the researching methods, we used scanning electron microscopy and atomic force microscopy as well as X-ray diffraction. There is a comparative analysis of data from these methods.